THE PROBLEM OF EMPLOYMENT AND UNEMPLOYMENT OF THE POPULATION IN WARTIME - VEDERNIKOV, Mykhailo; CHERNUSHKINA, Oksana; KRYVONYUK, Diana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the issues of employment and unemployment of the population in wartime. The essence of the concept of employment and unemployment has been defined in accordance with the current legislation. An analysis of the economically active population of Ukraine and Khmelnytskyi region was carried out according to the data of the State Statistics Service. The dynamics of labor force indicators by age categories in terms of division by gender in Ukraine as a whole and in the Khmelnytskyi region were studied. The results of the calculations showed slight differences in the indicators of Ukraine and Khmelnytskyi region in percentage terms. Negative trends in the labor market of Ukraine with a decrease in the indicators of the workforce and employed population and an increase in the number of persons classified as unemployed and persons not included in the labor force were noted. The indicators of the labor market of Ukraine during the period of the full-scale invasion are presented and analyzed based on the results of sociological research. Emphasis is placed on the implementation of measures to increase employment of the population in war and post-war times. Unemployment and employment of the population are an integral part of human life. In the conditions of the pre-war period, the issue of unemployment was the main problem of the labor market, therefore, a number of state support programs were created to overcome unemployment in Ukraine. During the war, the issue of unemployment only worsened. The results of the study of the dynamics of indicators of the economic activity of the population of Ukraine in general and Khmelnytskyi region, in particular, proved the similarity of the indicators of the economically active population of Ukraine and Khmelnytskyi region. According to the "labor force" indicator, there is a slight difference in the decrease in the number of the labor force in Ukraine and in the Khmelnytskyi region. According to the "employed population" category, there is an advantage of the reduction of this indicator in the Khmelnytskyi region over the indicator in Ukraine. According to the category of the unemployed population, there is a preponderance of the decrease in the number of unemployed in the Khmelnytskyi region over the indicators in Ukraine in the extreme periods of the study. Sociological surveys play an important role in labor market research. They help to find out the real state of economic activity of the country's population. The data of a complex sociological study reflect an increase in the number of the unemployed population by almost three times compared to the pre-war period. This increase was due to external and internal migrations of the population of Ukraine, closure of businesses and the inability of the population to work in a certain territory of Ukraine. However, business is starting to recover and the number of unemployed people is decreasing every month. In the western part of Ukraine, there is an increase in the equation of competition for a vacant position. A high level of unemployment is observed in the southern and eastern parts of Ukraine. In order to improve the situation on the labor market of Ukraine in the war and post-war periods, it is necessary to develop a strategy for motivating the employment of the population of Ukraine.
Keywords: employment; unemployment; economically active population; labor force; labor market